«The anime business»: the history of anime and general review of anime’s market (Journal of Oriental Studies, 2017)
In recent years, overseas Japanese animation was called “anime”. Animehas crossed the border, where it is called “comics for children” nowhas a high popularity among both adults and children. Define the anime“cartoon simple” - makes it impossible to show the variety of deep ofanime. In the anime products have all the elements, like a novel, drama,tragedy, comedy, history, residents of foreign countries that used to watchmovies. Anime affects some psychological topics that are not shown inthe Euro-American movies “- says Susan J. Napier.. But for most people inKazakhstan anime it is still children’s cartoon “exclusively for children.” Inthis regard, the article being acquainted, describes the anime as the onepart of Japanese culture, anime stories and being a general overview onthe anime market.